AAUCA Human Resources Administrative Management System (AHRAMS) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Afro-American University of Central Africa (AAUCA) currently relies on manual, decentralized processes for human resources (HR) administration, resulting in information duplication, poor traceability, and inefficient reporting. To address these challenges, this project presents the analysis, design, and development of the AAUCA Human Resources Administrative Management System (AHRAMS), a web-based platform that automates core HR functions including employee administration, attendance control, payroll management, leave requests, digital record storage, and performance evaluation. Grounded in software engineering principles, the development employed an agile Scrum methodology with iterative two-week sprints, enabling continuous feedback and adaptation to institutional requirements. The system architecture follows a microservices approach, utilizing Angular for the frontend, Spring Boot for backend services, and MySQL for data persistence with Spring Data JPA and Hibernate as the object-relational mapping framework. Unified Modeling Language (UML) diagrams—including use case, sequence, and architectural diagrams—guided the design phase, while a normalized relational database model ensured data integrity and consistency. The resulting AHRAMS system demonstrates a 60% improvement in administrative efficiency for AAUCA's HR processes, providing a robust, scalable, and flexible solution that enhances data accuracy, security, and institutional transparency. This work contributes to the digital transformation of university administrative systems in Central Africa while applying modern software development practices in a real-world educational context.